KUALITAS HIDUP PASIEN KANKER PAYUDARA DI RSUP DR. KARIADI SEMARANG MENGGUNAKAN KUISIONER EORTC QLQ-C30 - Marwin Marwin; Dyah Aryani Perwitasari; Susan Fitri Candradewi; Bayu Prio Septiantoro; Fredrick Dermawan Purba (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
ABSTRACT Breast cancer is the most common cancer found in women and is the dominant cancer in Indonesia. Cancer treatments such as chemotherapy can affect the quality of life of patients including physical, psychological, and social. The purpose of this study is to measure the quality of life of breast cancer patients. This research used cross sectional study design. The patient quality of life was measured using the EORTC QLQ-C30 questionnaire. The subjects of this study were breast cancer patients in RSUP Dr. Kariadi Semarang meeting the inclusion criteria. The cognitive function domain, social function, emotional function, role function, and physical function were 86,15 ± 17,82; 84,10 ± 21,13; 82,56 ± 17,72; 77,95 ± 29,77; 76,72 ± 22,95, respectively. Whereas in symptom scale group from pain, fatigue, insomnia, appetite loss, financial difficulties, nausea and vomiting, constipation, dyspnea and diarrhea were 32,82 ± 30,33; 32,65 ± 21,14; 31,79 ± 34,58; 31,79 ± 32,51; 30,77 ± 32,44; 23,59 ± 25,67; 17,95 ± 30,9; 4,62 ± 14,28; 4,10 ± 13,83, respectively. For global health status / quality of life obtained 72.18 ± 18.94. The highest score on the functional scale is the cognitive function domain and the lowest score is the physical function.On the scale of symptom the domain that has the highest score is the pain domain and the lowest score is the diarrhea domain. Keywords: quality of life, breast cancer, EORTC QLQ-C30